Cancer nursing research priorities: A rapid review. (April 2023) - Dowling, Maura; Efstathiou, Nikolaos; Drury, Amanda; Semple, Cherith; Fernández-Ortega, Paz; Brochstedt Dieperink, Karin; Pape, Eva; Kotronoulas, Grigorios; Miguel, Susana; Colomer-Lahiguera, Sara; Bağçivan, Gülcan
Abstract: Purpose: Identifying cancer nursing research priorities is central to influencing the direction of cancer care research. The aim of this rapid review was to explore research priorities identified by oncology nurses for cancer care delivery between 2019 and 2022. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis informed the design of the rapid review. MEDLINE, CINAHL, PUBMED, Web of Science, and Cochrane databases were searched for studies published between December 1st, 2018, and September 30th, 2022. This timeframe was chosen to account for the latest relevant evidence synthesis, as well as changes in cancer care necessitated by the COVID-19 pandemic. The Quality Assessment of Diverse Studies tool was used to appraise quality. Results: Four studies met the inclusion criteria. Many of the research priorities identified were influenced by the COVID-19 pandemic. The top cancer nursing research priority identified was the role of technology in improving patient and caregiver symptoms and health outcomes. Other most prevalent research priorities were focused on symptom management, culturally sensitive palliative and psychosocial care, early/integrated palliative care, financial toxicity, modifiable risk factors related to social determinants of health, public and patient involvement in research, and oncology nurses' well-being and scope of practice. Conclusion: The findings indicate a need to steer a strategic programme of cancer nursing research towards digitalisation in cancer care to meet the current needs of people living with cancer and their caregivers. However, cancer nurses' burnout, staff shortages and disparities in specialist education will hinder the implementation of certain models of care. Highlights: Six priority areas for cancer nursing research have been identified in this review. COVID-19 has influenced cancer nursing research priorities. The role of technology (including telehealth) in cancer care is a new priority.